2000
DOI: 10.1088/0957-0233/11/6/313
|View full text |Cite
|
Sign up to set email alerts
|

Research on the vortical and turbulent structures in the lobed jet flow using laser induced fluorescence and particle image velocimetry techniques

Abstract: The changes in vortical and turbulent structure in the near field (X/D < 3.0) of jet mixing flow caused by a lobed nozzle were investigated experimentally in the present study. The techniques of planar laser induced fluorescence and particle image velocimetry were used to accomplish flow visualization and velocity field measurements. The experimental results showed that, compared with a circular jet flow, lobed jet mixing flow was found to have a shorter laminar region, a smaller scale of the spanwise Kelvin-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…The mean streamwise profile of the convergent nozzle is flat (Fig.4 a) while for the Cross-Shaped nozzles, a two-step distribution characterized the major plane (Fig.4 a). The same behaviour was also observed by Nastase et al [52] in a free jet from a cross-shaped orifice and by Hu et al [53] in a six-lobed nozzle jet. This is because in the lobed jets, the major plane has two shear layers: the inner shear layer between the jet central core and the lobes, and the outer shear layer between the jet flow and its ambience.…”
Section: Initial Conditionssupporting
confidence: 83%
See 1 more Smart Citation
“…The mean streamwise profile of the convergent nozzle is flat (Fig.4 a) while for the Cross-Shaped nozzles, a two-step distribution characterized the major plane (Fig.4 a). The same behaviour was also observed by Nastase et al [52] in a free jet from a cross-shaped orifice and by Hu et al [53] in a six-lobed nozzle jet. This is because in the lobed jets, the major plane has two shear layers: the inner shear layer between the jet central core and the lobes, and the outer shear layer between the jet flow and its ambience.…”
Section: Initial Conditionssupporting
confidence: 83%
“…A wide region of intensive mixing characterized by high turbulence intensity (around 30% of W0) could be observed with jets from the CO/P and CO/H nozzles. Nearly identical turbulence profiles were measured by Hu et al [53] in their six-lobed jet.…”
Section: Initial Conditionssupporting
confidence: 75%
“…This behaviour was also reported by previous researchers in 3D lobed geometries. Hu et al [43] reported that the potential core region at the centre of their three-dimensional six-lobe jet flow was much smaller and shorter than that in the circular jet flow. However, as Nastase and Meslem [41] mentioned, it should be underlined that the performance of the lobed jet is not limited to its potential core region.…”
Section: Stagnation Valuesmentioning
confidence: 95%
“…Point measurements with hotwire anemometry have been extensively used to study, for example, the effect of nozzle shape on the mixing along the jet axis [8], characteristics of jet impingement cooling [9], the influence long slot nozzle geometry on a plane jet [10], and turbulence characteristics of jets from a triangular orifice [11]. Particle image velocimetry (PIV) has been used to investigate synthetic jets issuing from different non-circular nozzle shape at high Reynolds numbers [2], subcooled boiling in bubble-top jet flows [12,13], and lobed jets [14], among others. Tomographic PIV has also been used in planar jet flows to characterize 3D vortex structures [15].…”
Section: Introductionmentioning
confidence: 99%